Simulation-based optimal planning for material handling networks in mining. (March 2013) - Nageshwaraniyer, Sai Srinivas; Son, Young-Jun; Dessureault, Sean
A two-level hierarchical simulation-based framework is proposed for real-time planning in one of the largest coal mines in the world. At the coal mine, various decisions (e.g. truck locks, hopper-silo connections and silo blend values) have to be made to ship coal to customers via trains. To resolve machinery scheduling and train loading problems in an integrated manner, mathematical formulations are developed and embedded within the proposed hierarchical framework. At the upper level, the coal flow in the simulation model is directly from pits to trains and in the lower level a full simulation model of the coal mine is used for simulating the flow of coal from pits to hoppers via trucks, then from hoppers to silos and silos to loadouts via conveyors. In this work, Arena software is used for the simulation model: it retrieves real-time status and historical performance data from Microsoft SQL Server situated remotely at the coal mine. OptQuest software is used to resolve optimization problems. Finally, two types of experiments are conducted to illustrate the performance of the proposed framework for the actual coal mine. Firstly, the bounds of the constraints in the upper level are varied to study the behavior of the total revenue in shift and revenue by train. Secondly, the effects of increasing variations in truck travel times, loading and dumping rates on machine utilization are studied at the lower level.